Beer and Brewing in Medieval Culture and Contemporary Medievalism
XVII, 407 p. 26 illus.
Keywords: Representations of Beer in the Middle Ages: Beer Culture and Medievalisms is a cross-cultural analysis of the role that alcohol consumption played in literature, social and cultural history, and gender roles in the Middle Ages. The volume also seeks to correct or offer new insights into historical beer production. By drawing on the expertise of scholars of history, archaeology, Old and Middle English, Old Norse, and Medieval and Early Modern literature, the book produces a sustained discussion of how beer and alcohol consumption in the Middle Ages directly contributes to the romanticized vision of the medieval ale-hall omnipresent in beer marketing today. The essays describe alcohol consumption in the Middle Ages across much of Northern Europe, engage with the various myths employed in modern craft beer advertising and beer production, and examines how gender intersects with beer production and consumption. The editors also raise certain critical questions about medievalisms which need to be interrogated, particularly in light of the continued use of the Middle Ages for white supremacist and colonialist ideals. The volume contributes to the study of the popular and historical understandings of the Middle Ages as well the issues of race and gender. John A. Geck is Assistant Professor in the Department of English at the Memorial University of Newfoundland, Canada, where his research deals with transmissions of high and low culture in later medieval and early modern England, encompassing romance, hagiography, and drama; medievalisms and other projections of the medieval in popular and digital culture. Rosemary O’Neill is Associate Professor of English and Women’s and Gender Studies at Kenyon College, USA. Her research explores the intersection of economics and medieval literature, and she has published and forthcoming work on Langland; Chaucer; the figure of Judas in medievaldrama and poetry; and the resonances of medieval poetry in contemporary literature. Noelle Phillips is English Instructor at Douglas College, Canada. Her research engages in medieval book history, the work of Chaucer and Langland, the book collecting habits of the Earls of Northumberland, and most recently, the use of medievalism in marketing craft beer and breweries. Her recent book, Craft Beer Culture and Modern Medievalism: Brewing Dissent (2019) explores the stories and mythologies inherent to modern craft brewing. .